2019
DOI: 10.1002/fsn3.1161
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chitosan nanoparticles and fennel essential oils (Foeniculum vulgare) on the shelf life of Huso huso fish fillets during the storage

Abstract: Fish and fishery products are important parts of the human diet, but the microbial, chemical, and physical deteriorations limit their shelf life. Using the modified atmospheric packaging system and edible coatings is one of the main procedures to improve the shelf life of fish. In this research, the effect of chitosan nanoparticles (CNPs) loaded with fennel essential oils along with modified atmosphere packaging (MAP) system on chemical, microbial, and sensorial properties of Huso huso fish fillets during stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 61 publications
1
23
0
Order By: Relevance
“…On the 7th day (Table 3), MBC was remarkably decreased than MAL by about 2.1, and 2.0, log CFU/g, respectively for fish samples enclosed in S-AgNP/Ult.PVA and S-AgNP/Pho.PVA preserved at 4 °C while those of the control group (5.83 ± 0.05) showed no significant difference (P>0.05) compared to the MAL at the same conditions. The MBC reached 5.33 log CFU/g after 9d (Maghami et al, 2019) while the Huso huso fillets wrapped with chitosan-NPs activated with fennel essential oil (EO) relatively in agreement to this study showed the MBC was 3.86 ± 0.05 and 7.75 ± 0.02 log CFU/g in fish coated with S-AgNP/Ult.PVA with no significant difference (p>0.05) compared to those of S-AgNP/Pho.PVA on 7th and 14th day, respectively indicating that the MBC might be less than MAL (6 log CFU/g) and prolonged the shelf life up to 9th day, which was not analyzed in this study. Based on our previous study (Barani et al, 2018), LDPE/TiO2/Ag NPs could postpone the growth of mesophilic bacteria (6 log CFU/g) up to 14th day while its control reached this value on 6th day.…”
Section: Resultssupporting
confidence: 89%
“…On the 7th day (Table 3), MBC was remarkably decreased than MAL by about 2.1, and 2.0, log CFU/g, respectively for fish samples enclosed in S-AgNP/Ult.PVA and S-AgNP/Pho.PVA preserved at 4 °C while those of the control group (5.83 ± 0.05) showed no significant difference (P>0.05) compared to the MAL at the same conditions. The MBC reached 5.33 log CFU/g after 9d (Maghami et al, 2019) while the Huso huso fillets wrapped with chitosan-NPs activated with fennel essential oil (EO) relatively in agreement to this study showed the MBC was 3.86 ± 0.05 and 7.75 ± 0.02 log CFU/g in fish coated with S-AgNP/Ult.PVA with no significant difference (p>0.05) compared to those of S-AgNP/Pho.PVA on 7th and 14th day, respectively indicating that the MBC might be less than MAL (6 log CFU/g) and prolonged the shelf life up to 9th day, which was not analyzed in this study. Based on our previous study (Barani et al, 2018), LDPE/TiO2/Ag NPs could postpone the growth of mesophilic bacteria (6 log CFU/g) up to 14th day while its control reached this value on 6th day.…”
Section: Resultssupporting
confidence: 89%
“…22 Similarly, it was concluded that F. vulgare is an effective antibacterial agent against different bacteria in the form of aqueous extract. 23 antimicrobial properties are associated with bacterial susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…Hasani et al [ 72 ] reported that pomace extract significantly delayed psychrotrophic bacterial growth as well as TVC and TVB-N of refrigerated silver carp. Maghami et al [ 73 ] investigated the effect of chitosan nanoparticles (CNPs) loaded with fennel essential oil (FEO) in combination with MAP on microbial, chemical and sensorial properties of Huso huso fish fillets during refrigerated storage. Results showed that coating fish fillets with CNPs and FEO significantly reduced the PV, TVB-N and TBA values compared to the control samples.…”
Section: Innovative Seafood Preservation Methodsmentioning
confidence: 99%